1997
DOI: 10.1523/jneurosci.17-09-03322.1997
|View full text |Cite
|
Sign up to set email alerts
|

Glycinergic Inhibition Contributes to the Generation of Rostral Scratch Motor Patterns in the Turtle Spinal Cord

Abstract: Cutaneous stimulation within the rostral scratch receptive field in a low spinal-immobilized turtle elicits a fictive rostral scratch reflex characterized by robust rhythmic motor output from ipsilateral hindlimb muscle nerves and weaker, alternating motor discharge in contralateral nerves. Simultaneous bilateral stimulation elicits bilateral rostral scratch motor patterns in which activity on the right and left sides alternates.We investigated the role of glycinergic inhibition in the generation and coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 31 publications
7
27
0
Order By: Relevance
“…According to the ''bilateral shared core'' model (Stein et al 1995), HF and HE modules, comprising the core of the scratch rhythm generator, interact via crossed and uncrossed synaptic pathways: HF modules make reciprocal inhibitory connections with contralateral HF and ipsilateral HE modules and mutual excitatory connections with contralateral HE modules. These connections are supported by more recent studies (Currie 1997;Currie and Lee 1997;Stein et al 1998). We disconnected as much HE circuitry as possible from the right and left rostral scratch networks by completely transecting the spinal cord at the caudal end of segment D 9 or D 8 in the anterior enlargement; this created D 3 -D 9 and D 3 -D 8 preparations, respectively.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…According to the ''bilateral shared core'' model (Stein et al 1995), HF and HE modules, comprising the core of the scratch rhythm generator, interact via crossed and uncrossed synaptic pathways: HF modules make reciprocal inhibitory connections with contralateral HF and ipsilateral HE modules and mutual excitatory connections with contralateral HE modules. These connections are supported by more recent studies (Currie 1997;Currie and Lee 1997;Stein et al 1998). We disconnected as much HE circuitry as possible from the right and left rostral scratch networks by completely transecting the spinal cord at the caudal end of segment D 9 or D 8 in the anterior enlargement; this created D 3 -D 9 and D 3 -D 8 preparations, respectively.…”
Section: Introductionsupporting
confidence: 63%
“…In D 3 -end preparations (low spinal animals with a complete cord transection between segments D 2 and D 3 ), unilaterally evoked fictive rostral scratching is characterized by rhythmic alternation between ipsilateral hip flexor (HF) and hip extensor (HE) bursts and monoarticular knee extensor (KE) discharge during the late HF phase (Robertson et al 1985). There is also weaker rhythmic motor output from contralateral hindlimb (Currie and Lee 1997;Stein et al 1995Stein et al , 1998 and preenlargement (Currie and Gonsalves 1997) muscle nerves that alternates with ipsilateral activity. Simultaneous bilateral stimulation in the right and left rostral receptive fields elicits bilateral rostral scratch motor patterns in which homologous nerve activity alternates on the right and left sides (Currie and Gonsalves 1997;Currie and Lee 1997;Stein et al 1995Stein et al , 1998.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive evidence indicates that crossed commissural fibers in the turtle hindlimb enlargement can also contribute to right-left coordination during scratch reflex Gonsalves 1997, 1999;Currie and Lee 1997;Currie and Stein 1989;Stein et al 1995Stein et al , 1998, flexion reflex (Currie and Lee 1996), and chemically activated hindlimb motor patterns in isolated turtle spinal cords (Currie 1999). New experiments are needed to gauge the relative contributions of longitudinal (interenlargement) propriospinal and crossed commissural coordinating mechanisms during turtle locomotion and to identify and characterize the spinal interneurons that underlie these functions.…”
Section: Pathways Contributing To Interlimb Coordinationmentioning
confidence: 99%
“…NMDA and AMPA locally applied (hindlimb enlargement level in the spinal cord) were reported to activate the CPG for scratching in both in vivo and in vitro turtle preparations (Currie, 1999). It has also been shown that glycinergic mechanisms contribute to, but are not critically important for, maintaining an alternating interlimb coordination during bilateral scratch motor patterns (Currie and Lee, 1997). Endogenous glutamate released in the spinal cord during scratching was reported to contribute to hindlimb motoneuron depolarization via ionotropic and mGlu1 receptor activation and Ca v 1.3 voltage-gated calcium channelmediated conductances (Alaburda and Hounsgaard, 2003), and other not yet fully characterized high conductances (Alaburda et al, 2005).…”
Section: Scratchingmentioning
confidence: 99%